A time-orthogonal CDMA high-speed uplink data transmission scheme for 3G and beyond. - Khan, Farooq (IEEE Communications magazine)
In 3G systems, the achievable data rates and capacity on the uplink are much smaller than the downlink data rates and capacity due to the nonorthogonal nature of the CDMA uplink. In this article, we present a new time-orthogonal CDMA approach called high-speed uplink data burst transmission mode. The concept is based on slot-synchronized slot-orthogonal transmissions whereby high-speed data transmissions take place in slots orthogonal to the slots used for physical layer control signaling and low-data-rate transmission such as resource requests. Using this approach, very high data rates and capacity are achieved during data burst transmission because of the availability of high signal-to-interference-plus-noise ratio, resulting from the orthogonal nature of the transmissions. Simulation results show that the uplink spectral efficiency of the proposed scheme is approximately four times better than that achieved with the existing 3G systems.